Burkean identification: Rhetorical inquiry and literacy practices in social media - MacDonald, Lauren E; Walsh, Stephanie L (Journal of Interdisciplinary Studies in Education, 2014)
Through Facebook and Twitter, users now have communities alwaysalready available. The dynamic nature of these sites, constantly updating,changing, and shifting, allows for a rich exploration of the nature of self andcommunity. This paper examines such interactions within the “Parlour rooms” ofsocial networks, using Kenneth Burke’s theories on identity as a framework.These platforms offer opportunities for writing teachers to explore rhetoricalconcepts, develop students’ critical literacy skills, and foster collaborativelearning. Considered in the context of computer-mediated communications,Burke’s theories expand traditional notions of the rhetorical concept kairos and,as Cynthia Sheard (1993) notes, enrich our notions of what it means to bespatially, temporally, and rhetorically situated as writers and readers in thesedigital mediums.